2018
DOI: 10.1155/2018/2638258
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Counts in Mucosal Biopsies of the Ileum and Colon: Interobserver Variance Affects Diagnostic Accuracy

Abstract: Primary eosinophilic gastroenteritis and colitis (EGE) is a rare entity with unspecific clinical and endoscopic findings. Validated histopathologic criteria for confirming the diagnosis are lacking, because numeric values for normal or elevated concentrations of eosinophils in mucosal biopsies are varying between observers. To quantify this interobserver variance, we had the same set of 30 slides of eosinophilic-rich mucosal biopsies from the ileum and colon systematically reviewed by a panel of six independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It is desirable that a prospective study with a large number of cases be designed to confirm our findings and verify the importance of evaluating serum albumin and extensive disease. Second, it was reported that there is a high interobserver variance in counts of EI in the mucosa of the ileum and colon [28]. There is no standardized counting method for EI in the mucosa of the gastrointestinal tract, and this problem has not yet been resolved.…”
Section: Discussionmentioning
confidence: 99%
“…It is desirable that a prospective study with a large number of cases be designed to confirm our findings and verify the importance of evaluating serum albumin and extensive disease. Second, it was reported that there is a high interobserver variance in counts of EI in the mucosa of the ileum and colon [28]. There is no standardized counting method for EI in the mucosa of the gastrointestinal tract, and this problem has not yet been resolved.…”
Section: Discussionmentioning
confidence: 99%
“…International consensus concerning the upper cut-off limit of normal eosinophil infiltration has yet to be reached and no international guidelines have been published. Interobserver variance of eosinophil counts in gastrointestinal mucosal biopsy specimens has been reported to be not good enough [ 32 ]. Furthermore, the visual size of the microscopic HPF differs among types of microscopes, with a nearly four-times difference in some cases, which may cause difficulties with determining the eosinophil count for a diagnosis of EGID.…”
Section: Reviewmentioning
confidence: 99%
“…EGE is characterized by clusters of eosinophils in the mucosal lining, eosinophil accumulation, and the presence of intraepithelial eosinophils (9). EGE is distinct from the more well-known EoE for clinical purposes; however, both are thought to be triggered by T2-mediated food hypersensitivity (11). Additionally, because the clinical signs of EGE are non-specific, it might be difficult to diagnose patients (12).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, because the clinical signs of EGE are non-specific, it might be difficult to diagnose patients (12). Endoscopic reports are similarly uncharacteristic, mimicking other diseases (13) (11,14) EGIDs are now identified pathologically, practically, and exclusively by endoscopically acquired mucosal biopsies (2), demanding a broader insight into eosinophils' function in GI mucosal health and disease (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%